Design of Low Rolling Resistance Tire Structure Based on Region Energy Loss - Wang, Guolin; Wu, Xu; Liang, Chen; Yang, Jian (Recent Patents on Mechanical Engineering, 2018)
Background: The tire is the only part of a vehicle that makes contact with the road, and the tire's rolling resistance certainly affects the fuel consumption of the vehicle. In previous researches, Scholars have studied the influence of some parts of the tire structure on rolling resistance and available patents have used varying methods to design low rolling resistance tires. Objective: The aim of this research is to explore the relationship between region energy losses and rolling resistance, based on which, an optimize tire structure is proposed to reduce the rolling resistance. Methods: In this paper, the 2-D cross-section of radial tire 205/55R16 was divided into two region: the crown and the non-crown. Then, a model of the tire was established for the Finite Element Analysis (FEA). And finally, with various structural changes in different regions, a sensitivity analysis was conducted. Results: The results show that in either region where the structure is changed, the energy loss in the considered region is consistent with the rolling resistance. In the crown area, the contribution of tread structure to energy loss is nearly up to 69%, and the 2# belt width is more sensitive than 1# belt width. In the non-crown area, abrasion, carcass, apex and sidewall have the same effect on energy loss, which is about 30%. Compared with the abrasion height, the apex height shows higher sensitivity to energy loss in the non-crown region. Apex and sidewall energy loss increased with decreasing abrasion height, and with increasing apex height. Conclusion: For the energy loss in the crown region, tire tread plays a crucial role. Reducing the width of tire belt and height of the apex can effectively reduce energy loss, and appropriately increasing abrasion height can also reduce the rolling resistance. By carefully combining all the design methods mentioned, a final tire structure which can optimize the rolling resistance is proposed.
Keywords: optimum scheme